Survival Analysis of Turkish Patients With Systemic Lupus Erythematosus: Older Age at Diagnosis Affects Mortality - Döndü ÜSKÜDAR CANSU; Hava ÜSKÜDAR TEKE; Cengiz KORKMAZ (Archives of Rheumatology, 2017)
Objectives: This study aims to determine the rate, causes, and risk factors of mortality in Turkish systemic lupus erythematosus (SLE) patients and whether age at diagnosis has an effect on mortality or not. Patients and methods: We retrospectively analyzed the data from 221 patients (10 males, 211 females; mean age 41.5±13.5 years; range 18 to 74 years) who were followed-up due to the diagnosis of SLE in our department between January 1998 and March 2016. Detailed clinical findings, organ involvements, autoantibodies, and complement levels of the patients were recorded. Results: Of the entire group, 19 patients (8.6%) died. Mortality incidence rate was 1.05/100 patient-years. Most frequent causes of death were infections, ischemic cardiovascular and cerebrovascular diseases. Through univariate analysis, older age at diagnosis and a short duration of follow- up were identified as the only factors with an influence on mortality (p=0.004 and p=0.002, respectively). Beyond the mentioned factors, organ involvements in SLE, autoantibodies or antiphospholipid antibody syndrome were not found to have a relationship with mortality. Further analysis conducted on late-onset, defined as the patient age of 50 or above at diagnosis, versus adult-onset, defined as the diagnosis at an age of younger than 50 years, revealed a remarkably shorter survival in patients diagnosed after age of 50 (p=0.003). Cumulative five-year, 10-year, and 15-year survivals of patients were 91.9%, 90%, and 88.2%, respectively. Conclusion: We identified older age at diagnosis as an effective factor on mortality. SLE patients who are diagnosed at an older age should be more closely and meticulously followed-up than those diagnosed earlier in terms of their mortality risk.